Assessment of Rotational Speed and Plunge Rate on Lap Shear Strength of FSSW Joints of AA7075/Mild Steel. (25th May 2022) - Ramya, G.; Pounrajan, Subburam; Prasad, D. V. S. S. S. V.; Soni, Sanjay; Ravichandran, P.; Kosanam, Koushik; Gopala Gupta, Amara S. A. L. G.; Dinesh, P. M.; Kumar, Leevesh; Shaik, Bazani
Abstract : Friction stir spot welding (FSSW) is an upgraded version of the friction stir welding process. This welding process can be used to replace permanent and temporary fastens such as bolts and nuts, screws, rivets, and welds. FSSW can be utilized to replace steel rivets in aircraft structure fabrication due to the elimination of time required to complete the joints and special tools. Moreover, the joining of dissimilar joints is very difficult due to the formation of different proportions of intermetallic compounds in the weld region. A lot of process parameters may influence the quality of the joints. This investigation analyzes the effect of speed of tool rotation and plunge rate of tensile shear fracture load of AA7075 mild steel dissimilar metal joints. From the observation, the joint fabricated with a speed of tool rotation of 1000 rpm and a plunge rate of 6 mm/min yielded a maximum shear fracture load of 9.86 kN. This weld strength enhancement may be linked to the formation of dynamic recrystallization and density distribution of strengthening precipitates.